Single-cell sequencing analysis reveals cancer-associated pericyte subgroup in esophageal squamous cell carcinoma to predict prognosis - Xiong, Kai; Pan, Bing; Fang, Hao; Tao, Ziyou (Frontiers in Immunology, 2025)
BackgroundThe role of cancer-associated pericytes (CAPs) in tumor microenvironment (TME) suggests that they are potential targets for cancer treatment. The mechanism of CAP heterogeneity in esophageal squamous cell carcinoma (ESCC) remains unclear, which has limited the development of treatments for tumors through CAPs. Therefore, a comprehensive understanding of the classification, function, cellular communication and spatial distribution of CAP subpopulations in ESCC is urgently needed.MethodsThis study used large-sample single-cell transcriptome sequencing (scRNA-seq) data to investigate pericytes’ subpopulation characteristics, functions, upstream and downstream regulation and interactions with other components of the TME in the ESCC, and analyzed prognostically in conjunction with Bulk RNA-seq data. In addition, pericyte subpopulations were validated and their spatial distribution in the ESCC TME was observed by multiplex immunofluorescence. Drug prediction and molecular docking was further used to validate the medicinal value of drug targets.ResultsCAPs in the ESCC TME were found to be highly heterogeneous, and we identified six pericyte subtypes: c1_ARHGDIB, c2_BCAM, c3_LUM, c4_SOD2, c5_TYMS, and c6_KRT17, which have commonality in a part of their functions, and each of them has a major function to play, by having different strengths of interaction with different components in the TME. In addition, we found that c4_SOD2 was negatively correlated with prognosis, conversely, c5_TYMS was positively correlated with prognosis. The drug with a better effect on c5_TYMS was docetaxel (binding energy = -8.1, -8.7 kcal/mol); raloxifene may be more effective against c4_SOD2, although raloxifene has a slightly lower binding energy to SOD2 (-6.4 kcal/mol), it has a higher binding energy to PDGFRβ (-8.1 kcal/mol).ConclusionThe present study identified and discovered pericyte subpopulations that were significantly associated with prognosis, which provides new biomarkers for predicting patient prognosis and adds usable targets for immunotherapy, and it is also important for gaining insights into the composition of the TME in ESCC.